2000
DOI: 10.1046/j.1365-2052.2000.00605.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic distinctness of African, Asian and South American local chickens

Abstract: The genetic variability of various local chicken populations derived from Bolivia, India, Nigeria and Tanzania was evaluated with 22 microsatellites. Between two and 11 alleles per locus were detected. All populations showed high levels of heterozygosity with the lowest value of 45% for the population named Aseel from India and the highest value of 67% for Arusha from Tanzania. A dendrogram was constructed based on CHORD distance by upgMa analysis. Within this tree the populations were assorted according to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
68
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(100 citation statements)
references
References 16 publications
20
68
5
Order By: Relevance
“…This result showed that genetic diversity in the four indigenous chicken breeds was high. A similar result (0.45 -0.67) was reported by Wimmers et al (2000) for African, Asian and South American local chickens. However, the mean He recorded in this research is lower than that reported by Zhang et al (2002) in Chinese native chickens (0.63 -0.86) and by Shahbazi et al (2007) in Iranian native chickens (0.62 -0.74).…”
Section: Discussionsupporting
confidence: 76%
“…This result showed that genetic diversity in the four indigenous chicken breeds was high. A similar result (0.45 -0.67) was reported by Wimmers et al (2000) for African, Asian and South American local chickens. However, the mean He recorded in this research is lower than that reported by Zhang et al (2002) in Chinese native chickens (0.63 -0.86) and by Shahbazi et al (2007) in Iranian native chickens (0.62 -0.74).…”
Section: Discussionsupporting
confidence: 76%
“…As a result of the FAO's recommendation and their availability through genomic mapping, microsatellites have been widely used to characterise genetic diversity. Genetic distances calculated from microsatellite data have been advocated as an objective criterion for making conservation decisions (Barker, 1999;Wimmers et al, 2000). However, other authors have severely criticised this approach and emphasised that aspects such as adaptive features and traits of economic or scientific importance are infrequently available for genetic distance measures.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely agreed that genetic diversity can be depicted at molecular level and by the phenotype and the production performance descriptions (Berthouly, et al, 2008;Hillel, et al, 2003;Tixier-Boichard, et al, 2009;Wimmers, et al, 2000). In our previous study (Andres, et al, 2008), we stated that among 7 breeds and varieties the significantly highest proportion of yolk in the egg was from the Lilliputians from Pilchów.…”
Section: Discussionmentioning
confidence: 98%
“…The decision to classify a given population as a genetic resource should be drawn from its distinctiveness within a species, particularly expressed by genetic distance (Wimmers, et al, 2000). If the separateness between the representatives of bantams and large fowl is clear even on the basis of appearance, the determination of the relatedness between large local varieties of chickens and utility breeds must be revealed by the molecular markers genotyping.…”
Section: Discussionmentioning
confidence: 99%